UPAYA PEMERINTAH KOTA PEKANBARU DALAM MENGEMBANGKAN KAIN SONGKET SEBAGAI PRODUK UNGGULAN - Dinantia, Cintami Prima; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine Pekanbaru City Government's efforts in developing songket as a superior product. As for the background of this study is that the policy of development of songket not run well. Development of songket weaving has not led to the effort to preserve and popularize songket. Songket is only known in certain circles. This research applies the theory of the role of institutions, while the method used is the method of research with a qualitative approach. The data obtained with interviews and documentary data analysis to further analyzed by descriptive analysis method. This study shows that the development of Songket Weaving crafts made by the City of Pekanbaru has not gone well, walaunpun all coaching programs have been implemented but the results